Concurrent Delay dan Penyesuaian Harga pada Kontrak Multi-Years: Perspektif Hukum Konstruksi Indonesia - Sumantri, Mahfiar Fajar Akbar; Sami’an, S.; Hardjomuljadi, Sarwono (SIGn Jurnal Hukum, 2024)
This research examines the legal implications of concurrent delay in price adjustments in multi-year contracts within Indonesian construction projects. The absence of specific regulations concerning concurrent delay in Law Number 2 of 2017 and its implementing regulations creates legal uncertainty and has the potential to trigger disputes. This research aims to comprehensively analyze the legal and empirical aspects of concurrent delay and price adjustments. Employing a normative juridical approach and case studies of construction projects experiencing concurrent delay, this research analyzes relevant legislation, contract clauses, and dispute resolution practices. The results show that concurrent delay introduces complexities in allocating responsibility and calculating compensation, especially concerning overhead claims and price adjustments. The case studies reveal that the success of claims is highly dependent on the completeness of documentation and the strength of legal argumentation. Furthermore, this research emphasizes the importance of drafting anticipatory multi-year contracts and implementing effective risk management to mitigate the risks of concurrent delay. This research recommends the development of more comprehensive regulations on concurrent delay and encourages parties to prioritize dispute resolution through negotiation and mediation.